2012
DOI: 10.1021/la3030364
|View full text |Cite
|
Sign up to set email alerts
|

Glucan Adsorption on Mesoporous Carbon Nanoparticles: Effect of Chain Length and Internal Surface

Abstract: The adsorption of cellulose-derived long-chain (longer than ten glucose repeat units on size) glucans onto carbon-based acid catalysts for hydrolysis has long been hypothesized; however, to date, there is no information on whether such adsorption can occur and how glucan chain length influences adsorption. Herein, in this manuscript, we first describe how glucan chain length influences adsorption energetics, and use this to understand the adsorption of long-chain glucans onto mesoporous carbon nanoparticles (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
109
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(114 citation statements)
references
References 36 publications
5
109
0
Order By: Relevance
“…Ir improved the thermal stability and catalytic activity, and MC enhanced the dispersion of metals and the adsorption of substrates onto the catalyst surface. According to a recent report about adsorption of substrates onto MC by Katz et al, the longer the chain length of glucan becomes, the easier the glucan adsorbs onto the surface of MC [74]. The adsorption occurred by the CH-π interaction between hydrogens on the glucan molecule and aromatic rings of the MC surface.…”
Section: Hydrolytic Hydrogenation Of Cellulose To Sorbitolmentioning
confidence: 99%
“…Ir improved the thermal stability and catalytic activity, and MC enhanced the dispersion of metals and the adsorption of substrates onto the catalyst surface. According to a recent report about adsorption of substrates onto MC by Katz et al, the longer the chain length of glucan becomes, the easier the glucan adsorbs onto the surface of MC [74]. The adsorption occurred by the CH-π interaction between hydrogens on the glucan molecule and aromatic rings of the MC surface.…”
Section: Hydrolytic Hydrogenation Of Cellulose To Sorbitolmentioning
confidence: 99%
“…Chung, Katz, and co-workers reported that a mesoporous carbon with pore diameter of 3.2 nm adsorbed cello-oligosaccharides in a Langmuir manner. 53 The adsorption amount was as much as 667 mg g…”
Section: Adsorption Of Cellulosic Molecules On Carbonmentioning
confidence: 99%
“…61 It has been demonstrated that mesopores of carbon (3.2 nm) can accommodate large cellulose molecules but micropores of SiO 2 do not even when the highest degree of negative Gibbs energy change of covalent bonding (substitution of SiCl with SiOcellulose) is available. 50a, 53 We used a zeolite-templated carbon (ZTC) 62 possessing homogeneous micropores with 1.01.5 nm diameters. ZTC was added to an HCl solution of long-chain cellulose molecules (molecular weight = 3600), which resulted in up to 800 mg g ¹1 of uptake.…”
Section: ¹1mentioning
confidence: 99%
“…The yield of glucose strongly depended on types of carbon catalyst used. It is notable that the graphitic surface of carbon also plays a role in adsorbing the cellulosic molecules by van der Waals force, CH _ π hydrogen bonding, and hydrophobic interaction 22), 23) . Hence, both hydrophilic and hydrophobic groups on carbon are essential for superior performance of the catalyst.…”
Section: Conversion Of Cellulose By Heterogeneousmentioning
confidence: 99%